Working time flexibility in European companies. Establishment survey on working time 2004-2005 - Chung, Heejung; Kerkhofs, Marcel; Ester, Peter (Luxembourg, 2007)
"Working time arrangements can have a significant bearing on the efficiency and productivity of companies as well as the health, wellbeing and motivation of their employees. This report provides unique insight into the various working time flexibility arrangements currently in place in companies across Europe. It is based on analysing the findings of a large-scale, representative survey carried out in establishments with 10 or more employees in 21 European countries in 2004-5. The report looks at whether and how countries differ in their application of flexible working time systems. It analyses the perceived impact of such arrangements on company performance in terms of economic success and employment stability or growth."